Rancang Bangun Sistem Informasi Work Order Produksi Sparepart Kendaraan Motor Berbasis Dekstop - Manase Sahat H Simarangkir; Mohammad Bintang Saputra (LPPM Politeknik Enjinering Indorama, 2020)
Information systems have a very important role in managing and providing information in an activity or field. One of them is a work order production information system in a company. In managing production work orders at PT. Chandra Nugerah Cipta some still use Ms. Excel, so that in meeting the information needs in particular to obtain WO (work order) information on production, production WO report production and information systems for the entry and exit of goods for production needs have not run optimally, so companies still need a better system. The system development method in this study uses the waterfall method. While the system approach method uses a structured approach consisting of context diagrams, data flow diagrams, table relationships, or ERD (Entity Relationship Diagrams). Implementation and design of the program uses MySQL as a database and VB programming language. For application development. The results of this study are the creation of a work order production information system at PT. Chandra Nugerah Cipta, which can simplify and speed up the processing of production work order data, including the record of the release of goods (requestition) for production needs and the entry of finished goods (finish notice) from production by minimizing or even eliminating data processing errors Keywords: Work Order, Waterfall, Vb.Net, MySql, Finish Notice